The Effect of Relationship Marketing, Customer Engagement and Brand Trust in Increasing Purchase Decisions in Local Trading Company in Indonesia - Rahmat, Dafrian Nur; Silvianita, Anita; Rubiyanti, Nurafni; Widodo, Arry (AIBPM Publisher, 2024)
A trading company in Bandung experienced a 491% sales increase, prompting research into the factors behind this phenomenon. This study examined the influence of relationship marketing and customer engagement on purchase decisions, mediated by brand trust. The research used a quantitative, causal-descriptive approach with simple random sampling. From a population of product coordinators conducting direct sales and demonstrations, 320 respondents were selected using the Slovin formula. Data were analyzed using Structural Equation Modeling (SEM) with Smart-PLS 02. Results showed that relationship marketing positively and significantly influenced brand trust (t-statistic 9.845; p-value 0.000) and purchase decisions (t-statistic 32.167; p-value 0.000). Customer engagement also significantly impacted brand trust (t-statistic 10.106; p-value 0.000) and purchase decisions (t-statistic 2.103; p-value 0.036). However, brand trust did not significantly mediate the effects of relationship marketing and customer engagement on purchase decisions. The study concluded that relationship marketing had the strongest direct impact on purchase decisions. Companies are encouraged to prioritize relationship marketing and customer engagement strategies while strengthening brand trust to maximize long-term consumer loyalty.